Answer:
![w=(x-3y+1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sdwwgwchl5tvwzgjv301uqbcsfrl74r7ms.png)
Explanation:
The given expression is :
x = 3 (y + w) -1
We need to find the value of w in terms of x and y.
Solving RHS of the given expression :
x = 3y+3w-1
subtracting both sides 3y.
x-3y = 3y+3w-1 -3y
x-3y = 3w-1
Add 1 both sides
x-3y+1=3w-1+1
3w=x-3y+1
![w=(x-3y+1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sdwwgwchl5tvwzgjv301uqbcsfrl74r7ms.png)
Hence, the correct option is (c) "
i.e. w = StartFraction x minus 3 y + 1 Over 3 EndFraction.